Wireless charging system using spectral energy harvesting technique - Chandrasekharan Nataraj; Mahsoom Raseen Abdul Careem; Ravi Lakshmanan; Sathish Kumar Selvaperumal; Raed Abdulla (Institute of Advanced Engineering and Science, 2019)
This paper presented the energy harvester circuit to enable wireless charging method. The wireless RF spectrum is abundant and potent in the public locations, which can be used for energy harvesting purpose. This is supported by the fact that RF signals are ubiquitous and do not require propagation media of any sort. The system is developed using optimal antenna, matching circuit and charge pump circuit. The 2x2 array type patch antenna operated at 924 MHz is designed and simulated using High Frequency Simulator. The antenna works as a transducer to capture and measure the RF signals from freely available energy source. The field study was conducted at three different highly populated locations such as place of education, place of residence, and place of transport using Software Defined Radio (SDR). The respective acquired RF energy values are -10.45 dBFS (morning), -10.45 dBFS (noon), and -13.33 dBFS (night) at the place of transport for the demonstration purpose. The antenna parameters study also conducted and proved that the antenna gain is good which is greater than 6.6 dB and also return loss greater than -43dB. In addition, charge pump circuit is designed and shown to be capable of boosting the voltage more than 2.5 V easily at the different frequencies for wireless charging purpose.